Rebecca eaudiobook An american girl. - Dembar Greene, Jacqueline (American Girl: Rebecca., 2010)
In these six stories from the uplifting American Girl series, a young girl living in 1914 New York learns what it's like to grow up in the big city. Rebecca Rubin has big dreams of becoming an actress, but her parents don't think girls are cut out for performing. As Rebecca searches for alternatives, she finds new ways to fulfill dreams that she never thought possible.